The Architects’ Practice Knowledge, Expressions and Communications of Architectural Design Intentions in Southwest Nigeria - Olubi, Abiodun Rufus; Erebor, Emokpae Murphy (Advances in Social Sciences Research Journal, 2023)
This study investigates the knowledge of Architects in the practice of design intentions, communications, principles, and expressions of architectural design in selected Architectural practices to improve architectural design delivery in Southwest Nigeria. Data collection was enhanced with a structured questionnaire from 250 participants comprising practicing Architects at various levels. The survey data were analyzed by descriptive statistics and the key finding is that Architects’ practice knowledge of intentions, communications, principles, and expressions of architectural design in the study area is very high. Appreciably, 66.6% of the respondents use pure lines to communicate design intentions, 25% of the respondents communicate through forms and shapes while 4.2% of the respondents each use geometry and materials as elements of communication of architectural intentions. The Pearson Correlation analysis to establish relationships between the tested variables reveals significant relationships between the meaning of architecture and visual communication of architectural intentions (p < 0.05; r = 0.359). This study recommends that Architecture as a utilitarian art requires the effective and clear conveyance of thought through pure visuals, clear lines, forms, and materials to communicate clear intentions, culture, personality, and status as well as create an important human-environmental link.